(untitled) (New York, 2004)
This volume, sponsored by the American College of Emergency Physicians, is a comprehensive, practical, ready-reference for the ED physician. Content focuses on how to effectively and accurately diagnose and treat this unique population. Each chapter is structured as follows: High Yield Facts: a bulleted list of 5 high yield facts Introduction: definition of problem and relevancy to older population Epidemiology (if applicable): scope, incidence/prevalence, mortality Pathophysiology: causative factors, predispositions, risk factors, mechanisms of disease process or injury, organ systems affected and disease course Clinical Features: chief complaint, presenting symptoms key historical information, physical examination including general appearance, vital signs, specific findings, and associated findings Diagnosis and Differential: laboratory findings and ancillary testing (including indications for same and also predictive value of such tests, differential diagnosis Emergency Department Care and Disposition: immediate management priorities (overview), initial ED management (to include both pharmacological and non-pharmacological care of the patient), subsequent care (if applicable).
Keywords: Geriatrics,Emergency medicine,Geriatrics,Emergency Medicine,Emergencies,Tình trạng khẩn cấp,Thuốc dùng cho khẩn cấp,Lão khoa,Lão khoa,Thuốc dùng cho khẩn cấp; Methods,Methods,Aged,Người lớn tuổi,Phương pháp,Phương pháp